Evaluation of major cereal crops for resistance against Rhizoctonia solani under green house and field conditions - DEEPTI SRIVASTAVA, PRAMILA PANDEY and K.N. SINGH*, MD. SHAMIM, DEEPAK KUMAR (Indian Phytopathology, 2014)
A wide collection of cultivated rice, wild rice, maize, wheat and barley genotypes were screened against R. solani for resistance. Results showed that none of the tested cultivated rice varieties showed resistance to sheath blight, except wild rice accessions, Oryza australiensis and O. grandiglumis. Only two rice cvs., IR 42 and TKM 9 showed moderate resistance among the cultivated rice varieties screened. Moderate resistance was also observed in barley cv. NDB 1445, while other hosts showed susceptibility to the disease. Different hosts included in this study were grouped into two major clusters on the basis of distance based analysis. Two wild rice accessions O. australiensis and O. grandiglumis clustered separately than other hosts including the wild relatives. This study can further be utilized to understand the résistance mechanism in wild rice accessions as well as to take breeding programme with moderate resistance rice varieties.